MacMock tool development : Method to design loose lashing systems for container ships - Laine, Juuso (My University, 2023)
“MacMock tool development” is a Master’s thesis describing the process of developing a new tool and working method for designing container ship lashing systems. Multiple studies in maritime field focus on strength analysis and how to model dynamic forces on board. There are no studies on how to form a lashing system, and as container ships have grown bigger over the past decades, their container lashing systems have become increasingly complex. Traditional design methods have not allowed the designers to see and verify their designs in three-dimensional space before physical testing with actual steel equipment. The topic of this thesis is to develop a new tool and method for lashing designers to be able to carry out their tasks effectively in the future as well. The thesis was commissioned by MacGregor Finland and the case project was carried out from the spring of 2021 to the spring of 2022. MacGregor is a global company that designs and sells a wide range of cargo ship equipment. The goal of the case project was to develop a 3D CAD tool with a Graphical User Interface for designing lashing systems. With the tool, designs can be reviewed without having to prepare practical hardware tests. After initial introduction and literary review to the topic, the thesis presents the case project and its relevant design principles. Acceptable solutions to customer needs are determined using Axiomatic Design process. Based on the Axiomatic Design results, a 3D assembly with easy-to-use interface is developed to fulfil the customer needs. The case project presents the results of 3D model making and programming script for an interface. The development process is considered successful as all the customer needs can be fulfilled with the product. However, there still remains some shortcomings with the product that hinder its uses and some feedback from its future users is needed in order to adjust the tool to better serve its intended purpose. Still, already in its development phase the tool has drastically changed the design methodology of lashing systems at the company, and acts as the first step of direct three-dimensional design.
Keywords: 3D design, Macro script, Interface, SolidWorks, Axiomatic Design, Development